Impressions of an Overseas Visit by a Lines Engineer - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2018)
A fascinating paper from 1961 contrasting the technical and general differences in providing telecommunications services in Europe, North America and Australia.